Resiliência, estresse e recuperação em atletas paralímpicos na fase pré-competitiva - Freire, G. L. M.; Fiorese, L.; de Moraes, J. F. V. N.; da Silva Xavier, S. E.; de Oliveira, D. V.; do Nascimento Júnior, J. R. A. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2025)
This study investigated whether the level of resilience of Paralympic athletics athletes in a pre-competitive period was impacted by sociodemographic and stress variables. 107 Paralympic athletics athletes (92 men and 15 women) with a mean age of 32.25 ± 12.80 years participated in a regional championship. The instruments used were the Connor-Davidson Resilience Scale (CD-RISC) and the Sport Stress and Recovery Questionnaire (RESTQ-76 Sport). Data were analyzed using cluster analysis, chi-square test and multivariate analysis of variance (p <.05). The results revealed that there was no difference between the sociodemographic and stress variables in relation to the resilience profile. Compared with the low resilience cluster, the high resilience Paralympic athletics athletes had higher scores for the global recovery score (p=.023). It was concluded that sociodemographic and stress variables do not seem to be intervening factors for the level of resilience, but resilience seems to be an intervening factor for the recovery of Paralympic athletics athletes in the pre-competitive period.